Highly Stable and Active Pt/Nb-TiO2 Carbon-Free Electrocatalyst for Proton Exchange Membrane Fuel Cells - Shuhui Sun; Gaixia Zhang; Xueliang Sun; Mei Cai; Martin Ruthkosky (Journal of Nanotechnology)
The current materials used in proton exchange membrane fuel cells (PEMFCs) are not sufficiently durable for commercial deployment. One of the major challenges lies in the development of an inexpensive, efficient, and highly durable and active electrocatalyst. Here a new type of carbon-free Pt/Nb-TiO2 electrocatalyst has been reported. Mesoporous Nb-TiO2 hollow spheres were synthesized by the sol-gel method using polystyrene (PS) sphere templates. Pt nanoparticles (NPs) were then deposited onto mesoporous Nb-TiO2 hollow spheres via a simple wet-chemical route in aqueous solution, without the need for surfactants or potentiostats. The growth densities of Pt NPs on Nb-TiO2 supports could be easily modulated by simply adjusting the experimental parameters. Electrochemical studies of Pt/Nb-TiO2 show much enhanced activity and stability than commercial E-TEK Pt/C catalyst. PtNP/Nb-TiO2 is a promising new cathode catalyst for PEMFC applications.